Pascal Grouiez, Les stratégies des communautés et la régulation sectorielle et territoriale des configurations productives : le cas de l’agroalimentaire russe - Pascal Grouiez (Revue de la Régulation)
The end of the soviet system led to a reorganization of former kolkhozes and sovkhozes in Russia. Despite these transformations, the agricultural operators have developed strategies to preserve their non-market goods production. The decision to keep the former social role question the experts. Indeed, these behaviors create a priori less efficient economic performances, which should lead these enterprises to disappear. However, these strategies helps to maintain large corporate farms, which should not be compatible with the market (because of the economies of scale). This way, Russian agriculture became heterogeneous, while the reforms should have mainly helped only the emergence of small farms. Our main thesis is that a sectoral regulationist approach, which considers that the actor have a specific rationality links to the fact that this actor is also a member of a community, is able to analyze the choice to product some non market goods. To analyze the regulation we have used the concept of “productive configuration” saw as a representation of the framework which organizes the coherence of some institutional elements (as rules, political choices, territorial issues, market rules...). Ours empirical works in the oblast of Orel allowed us to represent the regulation of the agricultural sector as four “productive configurations”. We explained the plurality of the configurations as the result of the diversity of agreements consented by heterogeneous actors. These agreements allow each actor to maximize his interests according to his power and to reproduce the community to which he belongs to. To defend their individual and collective interests the actors create some legal structures on the land market which prevent the standard capitalism development in the Russian agriculture. These legal structures are based on the construction of the land as a collective patrimony.